Frequency, Causative Organisms, Excess Cost and Short-Term Outcomes of Peripheral and Central Line Associated Nosocomial Blood Stream Infection in Adult Patients Admitted in a Tertiary Care Hospital - Muhammad Owais Khan, Naseem Salah Uddin, Aiman Mahmood Khamisani, Rabeea Shah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hospital acquired Blood Stream Infections is one of the major type of nosocomial infection. As compared to 1.3-2.1 per 1000 central line days in high income nations, CLABSI occurs more frequently in middle- and low-income countries, with rates ranging from 7.4 to 12.2 per 1000 central line days. The incidence of both type of BSI is also reported to be different in different regions. Staphylococcus aureus, E. coli, enterococcus species, and candida species are some examples of common causative organisms. Objective: The primary objective: To study the incidence of CLABSI per 1000 line days among patients with inserted central line during hospital stay To study the incidence of PLABSI per 1000 line days among patients with inserted peripheral line during hospital stay The secondary objective: Frequent pathogens isolated from patients Additional length of stay in patients with blood stream infection (CLABSI and PLABSI) Excess cost incurred from excess investigations and medications Material and Methods: Total 250 patients of age ≥15 years and acquired CLABSI or PLABSI during hospital stay after 48 hours of admission were included. Sensitivities of the cultured organism were recorded. Antibiotics and other drugs for management of blood stream infection were recorded with dosage, duration and excess cost. Excess length of hospital stay due to blood stream infection along with total length of in hospital stay was checked. Finally outcome of every patient was analyzed. Descriptive statistics were calculated. Independent T test / Man Whitney U test was applied to compare the length of hospital stay and cost among patients with and without BSI (CLABSI/PLABSI). P value of less than or equal to 0.05 was considered significant. Results: There were 44% male and 56% female patients. Mean hospital stay was 11.30±7.24 days. Mortality rate was 17.2% while 8.8% patients were found with infection. Most common isolated organisms were pseudomonas (31.8%), staphylococcus aureus (18.2%), klebsiella (9.1%), acenatobacter (9.1%) and candida tropicalis (9.1%). Sixteen patients have excess hospital stay from infection acquisition day with average of 9.31±4.97 days. Majority (40.9%) of patients spends more than 35,000 PKR (7,062 PKR to 70,988 PKR) as excess cost in terms of treatment. Mortality rate among infected patients was 50%. Conclusion: Patients had to bear a heavy burden as a result of infections contracted when using central venous catheters, which lengthened hospital stays and raised treatment costs. Keywords: Central line, Peripheral, Blood Stream Infections, pathogens, length of stay, excess cost